Prediktor perundungan siswa sekolah dasar - Borualogo, Ihsana Sabriani; Wahyudi, Hedi; Kusdiyati, Sulisworo; Dwi Sulisworo (University of Muhammadiyah Malang, 2020)
Objectives: bullying is a serious problem which affected children negatively. The aim of this study was to explore predictor of bullying in elementary students in Kota Bandung. This is very crucial to know factors which contribute bullying cases in elementary students. By knowing predictors of bullying, we will be able to prevent bullying cases rising in children.Method: samples were 809 elementary students in Kota Bandung which chosen by stratified cluster random sampling from 11 elementary schools. There were 47.6% girls and 52.4% boysFindings: personal belief which support aggression was a predictor of physical, verbal, and psychological bullying. Conclusions: Father who rejected children was a predictor of physical bullying, while mother who rejected children was a predictor of psychological bullying. Unavailability of the father contributed twice bigger in the probability of the children being bullied.